Improving the availability of trade finance in developing countries: An assessment of remaining gaps - Marc Auboin (World Trade Organization (WTO), 2015)
While conditions in trade finance markets returned to normality in the main routes of trade, the structural difficulties of poor countries in accessing trade finance have not disappeared - and might have been worsened during and after the global financial crisis. In fact, there is a consistent flow of information indicating that trade finance markets have remained characterized by a greater selectivity in risk-taking and flight to "quality" customers. In that environment, the lower end of the market has been struggling to obtain affordable finance, with the smaller companies in the smaller, poorer countries most affected. In an area where statistics are difficult to find, this paper looks at recent available information and provides background on the persistent and significant market gaps for trade finance in developing countries, notably in Africa and developing Asia. It discusses various initiatives in which the WTO and partner institutions are involved to alleviate in part this situation.
Keywords: F13; F34; F36; O19; G21; G32; 330; trade financing; cooperation with international financial institutions; coherence; G-20; developing countries